Tahlil al akhtho' al-syaai'ah fi al-ta'biir al-syafawiy min naahiyyati al-qowaa'id lada tholabati qismi al-lughah al'arabiyyah wa aadabiha kulliyyati al-adab wa al-'uluum al-insaniyyah - Fery Saputra (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Foreign language learners in achieving language mastery often commit errors. In both spoken and written languages. They consisted of a mismatch between the language system produced and the target language system. The method used in this study is an analistic descriptive method. To illustrate fault forms, it is necessary to analyze errors by laying out the sources for error and the ideal steps to correct them. As for the results of the analysis there are oral errors and also the writing of student literature and language studies programs both from In the linguistic classification, the researcher finds grammatical and morphological errors, and in the surface classification the researcher finds errors in second-language acquisition in omission, increment, mode distortion, and forward and delay.